3D model magneto-acoustic waves in coronal loops observed during transient events - Sandra Milena Conde Cuellar (Instituto Nacional de Pesquisas Espaciais (INPE), 2017)
We present a three-dimensional analysis of magneto-acoustic waves, along the seven coronal loops, observed on the active region NOAA 11272 during the class B and C flares. We found 19-, 9-, 5-, 2-, 1-, and 0.6-minute waves using the pixelised wavelet filtering method over images obtained from the Atmospheric Imaging Assembly instrument. We modelled the velocity of these waves along the extrapolated magnetic field lines that reproduce the observed loops in extreme ultraviolet. The extrapolation was made over magnetograms, got from the Helioseismic and Magnetic Imager instrument, using the linear force-free approximation. From our model, we found temperatures 10$^{3}$ (maior equivalente) T (menor equivalente) 1.8 x 10$^{7}$ K and densities 10$^{7}$ (maior equivalente) n (menor equivalente) 10$^{17}$ cm$^{−3}$, covering from photosphere to corona, as expected in the solar atmosphere. Hence, we obtained acoustic c$_{s}$ $≈$ 10$^{2}$ km s$^{−1}$ and Alfvénic $υ$$_{A}$ $≈$ 10$^{4}$ km s$^{−1}$ velocities values which are in agreement with the literature. In addition, the brightness asymmetry observed along the coronal loops is explained by the magnetic field and Alfvén velocity distributions along the extrapolated field lines. We found fast magneto-acoustic waves at the beginning of B3.8 and C1.9 flares and slow modes along the loops during all flares. Our 3D model represents an unprecedented method to study waves in coronal loops. All results are coherent with expected values in the solar atmosphere conditions. === Apresentamos uma análise tridimensional de ondas magnetoacústicas ao longo de sete loops coronais, observados na região ativa NOAA 11272 durante os flares de classe B e C. Encontramos ondas de 19, 9, 5, 2, 1 e 0.6 minutos usando o método Pixelised Wavelet Filtering sobre imagens obtidas com o instrumento Atmospheric Imaging Assembly. Modelamos as velocidades dessas ondas ao longo das linhas de campo magnético extrapoladas que reproduzem os loops observados em ultravioleta extremo. A extrapolação foi feita sobre os magnetogramas obtidos com o instrumento Helioseismic and Magnetic Imager, usando a aproximação Linear Force-Free. A partir do nosso modelo, encontramos temperaturas de 10$^{3}$ (maior equivalente) T (menor equivalente) 1.8 x 10$^{7}$ K e densidades de 10$^{7}$ (maior equivalente) n (menor equivalente) 10$^{17}$ cm$^{−3}$, cobrindo desde a fotosfera até a coroa, como esperado na atmosfera solar. Desta forma, obtivemos valores para as velocidades acústica e Alfvénica de c$_{s}$ $≈$ 10$^{2}$ km s$^{−1}$ e $υ$$_{A}$ $≈$ 10$^{4}$ km s$^{−1}$ respectivamente, as quais estão acorde com a literatura. Adicionalmente, a assimetria no brilho observada ao longo dos loops coronais é explicada pelas distribuições do campo magnético e da velocidade Alfvén ao longo das linhas extrapoladas. Nós encontramos ondas magnetoacústicas rápidas no inicio dos flares B3.8 e C1.9 e modos lentos ao longo dos loops durante todos os flares. O nosso modelo representa um método inédito para estudar ondas em loops coronais. Todos os resultados são coerentes com os valores esperados nas condições da atmosfera solar.